Peningkatan Pengetahuan Remaja Putri Tentang Anemia dan Pentingnya Konsumsi Tablet Tambah Darah Pada Siswi MTs N 1 Sumbawa - Fitri Setianingsih; Yunita Lestari; Galuh Permatasari; Desy Fadilah Adina Putri (Fakultas Teknik Universitas Cenderawasih, 2023)
Anemia is a health problem throughout the world, especially in developing countries where an estimated 30% of the world's population suffers from anemia. In Indonesia, one of the problems faced by adolescents is the problem of micronutrient nutrition, namely around 12% of male adolescents and 23% of female adolescents experience anemia, which is mostly due to iron deficiency (iron deficiency anemia. Anemia in adolescents specifically experienced by female adolescents will have a more serious impact, considering they are prospective mothers who will become pregnant and give birth to a baby, thus increasing the risk of maternal death, premature birth and low birth weight babies (LBW).The government has a routine program related to the distribution of iron tablets for women of childbearing age (WUS ), including adolescents and pregnant women. To support this program requires a good understanding for young women regarding anemia and the importance of blood-supplementing tablets, one of which is providing counseling to students at MTs N 1 Sumbawa with the aim of increasing knowledge about the dangers of anemia and the importance of taking tablets added blood. This community service activity was carried out on May 26 with the result that the knowledge and understanding of students about anemia was getting better, students also knew that taking iron tablets was important. Students are also motivated to meet their nutritional needs and increase adherence in taking iron tablets regularly.